VALIDITAS PENGEMBANGAN LKS BERBASIS SQ3R PADA MATERI BANGUN RUANG SISI DATAR DI SMP - Prima Yudhi Prima Yudhi (FKIP UMSB, 2018)
The use of Student Worksheets (LKS) in mathematics learning, can train students to actively build their understanding by empowering their prior knowledge, and can improve students' memory independently based on an understanding of reading. To be developed SQ3R-based LKS that enables students to study systematically, effectively, and efficiently. Students can learn repeatedly to study teaching material from the stage of researching reading or teaching material (Survey), asking (Question), reading or studying (Reading), telling or rewriting (Recite), and reviewing (Review). This development research aims to produce SQ3R-based LKS for class VIII junior high school students on the subject of Building Flat-Side Space. The development model uses the McKenny model which consists of three stages, namely define, prototyping, and assessment. Based on the analysis of the results of the LKS validation, it shows that the development of SQ3R-based LKS is categorized as valid. Keywords: Validity, LKS, SQ3R, Build Space